Młodzieńcze wiersze miłosne Reymonta i ich adresatka - Samborska-Kukuć, Dorota (Poznańskie Studia Polonistyczne. Seria Literacka, 2023)
Reymont’s unpublished letters noted down in a special notebook of his called Marzenia (Dreams) are his juvenilia that lack much literary value, yet witness the future Nobel Prize laureate’s struggles with poetry which would never become part of his work as he would find himself most skilled in writing prose. What is important in Reymont’s letters, however, are the signatures of his personality, his characteristic style of expression and traces of his readings. The early lyrical texts reflect his emotional experiences from the time of writing and contain traces of the people he met, especially Wiktoria Słupska, the love of his youth, to whom the volume of poems was dedicated. Recalling these poems became a chance to reconstruct Reymont’s biography from his stay in Warsaw at the time of his fascination with theatre and spending time with the Woliński family.